Dynamic distortion simulations for curved aeronautical intakes - Chiereghin, Nicola; MacManus, David G.; Savill, Mark; Dupuis, Romain (Royal Aeronautical Society (RAeS), 2015)
This research focuses on the numerical simulation of the dynamic distortion in highly convoluted aeronautic intakes and extends the current knowledge with a systematic study of the influence of duct diameter, Mach number and offset. A comparison against experimental data revealed the capability of Delayed Detached Eddy Simulation to reproduce the trends of variation of distortion descriptors and pressure recovery although the absolute values are not yet captured. Analysis of the temporal distribution of the flow parameters identified the relevant fluctuating components both for total pressure distortion and swirl. A Proper Orthogonal Decomposition of the flow highlighted important differences of the major flow structures for different duct curvatures and a strong dependence of the distortion parameters also on the finer flow structures.
Keywords: Convoluted intakes; CFD; Detached Eddy Simulation; flow distortion; S-duct; Proper Orthogonal Decomposition